KEPATUHAN PENGAMBILAN ULANG OBAT ANTI HIPERTENSI PASIEN HIPERTENSI RUJUK BALIK DI APOTEK APPO FARMA BANJARMASIN - Erna Prihandiwati; Yugo Susanto; Riza Alfian; Maya Sari; Leonov Rianto (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Complications of hypertension in the body's organs cause a high mortality rate. Hypertension requires long-term drug therapy so that patients must adhere to treatment. One type of adherence in the treatment of hypertension is adherence to taking drugs from health care facilities so that patients always have the availability of drugs to drink. The purpose of this study was to examine the adherence to taking antihypertensive drugs in patients with hypertension who were referred back at the Appo Farma Pharmacy Banjarmasin. The study used an observational design. Data collection was carried out retrospectively. Data were collected from patient prescriptions for referrals at the Appo Farma Pharmacy Banjarmasin in the period May-June 2022. A total of 123 samples were used in this study. The sampling method used simple random sampling technique. Data on adherence to drug taking was analyzed using the Medication Possession Ratio (MPR) method. The parameters of the MPR calculation results are divided into compliant categories if 80% and non-compliant if less than 80%. The research data is displayed descriptively. The results showed that the measurement of adherence to repeated drug taking with a period of 3 months and 6 months were both dominated by samples with the category of adherence to taking medication again with a total of 103 samples (83.74%). Based on these data, it can be concluded that the samples of hypertensive patients in this study were not all adherence in taking their antihypertensive drugs.